An Advanced Molecular Detection Roadmap for Nonlaboratorians - Jessica N. Ricaldi; J. Todd Parker; Nathelia Barnes; Hannah Turner; Scott Santibañez (Emerging Infectious Diseases)
This article, aimed at nonlaboratorians such as healthcare providers, public health professionals, and policymakers, provides basic concepts and terminology to enable better understanding of other manuscripts in this advanced molecular detection journal supplement. This article focuses on 3 aspects of advanced molecular detection: pathogen genomics, bioinformatics, and public health application, while providing additional resources for understanding.